Quantitative pupillometry as a sensitive biomarker for detecting subtle neurological impairment in mild traumatic brain injury: a pilot study - Mitschang, Dorothea; Sydorenko, Viktoriya; Kühlwein, Daniel; Beynon, Christopher; Younsi, Alexander; Krieg, Sandro; Lenga, Pavlina (Neurological sciences, 2025)
Mild traumatic brain injury accounts for roughly 55 million trauma cases globally each year. However, diagnosis and management remain challenging as conventional methods like cranial CT and the Glasgow Coma Scale do not reliably detect subtle neurological impairments. Quantitative Pupillometry has shown promise in severe traumatic brain injury, but data on its use in mild traumatic brain injury is limited. This study aims to evaluate whether Quantitative Pupillometry can detect subtle neurological dysfunction in patients with mild traumatic brain injury.
Online veröffenticht: 13. August 2025
Gesehen am 28.10.2025